What did Joseph Wright mean by meaning: The complexity of lexical semantics in the English Dialect Dictionary Online - Markus, Manfred (International Journal of English Studies, 2020)
EDD Online, the online version of Joseph Wright’s English Dialect Dictionary, was completed by a project team at the University of Innsbruck in 2019. The sophisticated search-engine of the new interface 3.0 reveals the multi-faceted role of semantics in dialect words. Its complexity is due to both the fuzziness of lexical forms and the ambiguity of their meanings. This paper, beyond the theory-biased “complexity debate”, supports the opinion that traditional regional dialects, qua low-contact varieties, have developed a higher degree of lexical complexity than high-contact varieties, i.e. pidgins and creoles, and, in terms of word formation, than the Standard variety of English. The paper first discusses the often polysemous or homophonous meanings of headwords, then of strings within word compositions and phrases. The lemmas also sometimes turn out to be (bound) morphemes or variants. A major aspect in this paper is the wealth of figurative meanings in dialect. This is simply due to the essential role of iconicity, that is, a result of the fact that dialect speakers (“people”) want to “see” in their minds what they mean.